2020
DOI: 10.1101/2020.06.09.139246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling lactate-acetate conversion to butyrate by intestinalAnaerobutyricumandAnaerostipesspecies

Abstract: 24The D-and L-forms of lactate are important fermentation metabolites produced by intestinal 25 bacteria but have been found to negatively affect mucosal barrier function and human health. 26Of interest, both enantiomers of lactate can be converted with acetate into the presumed 27 beneficial butyrate by a phylogenetically related group of anaerobes, including 28Anaerobutyricum and Anaerostipes spp. This is a low energy yielding process with a partially 29 unknown pathway in Anaerobutyricum and Anaerostipes sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
(20 reference statements)
2
5
0
1
Order By: Relevance
“…This can be explained by the significant transcriptional activity for lactate consumption primarily via the lctABCDE pathway (Supplementary FigureS10). A. soehngenii showed high transcriptional activity for utilization of lactate plus acetate which further confirms our previous observation of this being a specialized niche for this organism(Shetty 2019;Shetty et al 2020). C. catus demonstrated activity for lactate consumption but is known only to consume the L-form of lactate, while A. soehngenii can use both the D-and L-forms of…”
supporting
confidence: 88%
“…This can be explained by the significant transcriptional activity for lactate consumption primarily via the lctABCDE pathway (Supplementary FigureS10). A. soehngenii showed high transcriptional activity for utilization of lactate plus acetate which further confirms our previous observation of this being a specialized niche for this organism(Shetty 2019;Shetty et al 2020). C. catus demonstrated activity for lactate consumption but is known only to consume the L-form of lactate, while A. soehngenii can use both the D-and L-forms of…”
supporting
confidence: 88%
“…soehngenii corresponds to five genes of the lct gene cluster identified previously in Acetobacterium woodii, which is an acetogen that has been shown to convert lactate to pyruvate via a mechanism involving electron confurcation [22]. Products of this lct gene cluster were recently detected by proteomic analysis [26], and the cluster reported in the related lactateutilizing species A. hallii, A. rhamnosivorans and Anaerostipes caccae. Five of the six clustered genes are also present in Anaerostipes hadrus, but all strains of this species with sequenced genomes examined here lacked the lactate racemase (lctF), thus explaining why they can only utilize D-lactate.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, we identify two gene clusters whose transcription is upregulated during growth with lactate as carbon and energy source. One of these corresponds to the lct gene cluster of A. woodii [22] that was recently identified from proteomic analysis in A. soehngenii [26] while the second encodes activities involved in the acrylate pathway of Coprococcus catus. This investigation reveals differences in the regulation, phylogenetic distribution and metabolic function of these two clusters, and provides novel insights into the mechanistic basis of different lactateutilization strategies used by human gut bacteria.…”
Section: Impact Statement Introductionmentioning
confidence: 99%
“…The observed positive effects of A. soehngenii are likely derived from the beneficial metabolites that were produced by this strain as a subsequent placebo-controlled mode-of-action trial showed that A. soehngenii L2-7 duodenal perfusion in metabolic syndrome subjects increased local gene expression and systemic GLP-1 levels, secondary bile acids and insulin sensitivity [129]. A. soehngenii is known to have a versatile metabolism that it is able to grow in a broad range of substrates including mono-saccharides as well as intermediates produced by intestinal microbes, such as lactate and acetate [130]. Lactate and acetate are substantially produced and quickly used by small intestinal microbes [131].…”
Section: Potential Next Generation Of Therapeutic Bacteria For Treatm...mentioning
confidence: 99%